A (des)continuidade do cuidado ao recém-nascido pré-termo em região de fronteira - Berres, Rosilene (2017)
The neonatal component has relevance in infant mortality rates, with prematurity being one of the main causes. Prematurity requires that the care of preterm infants be started in the hospital environment and be continued after leaving the health care environment. It is a qualitative study using the Grounded Theory as a methodological reference and the Complexity Theory as theoretical reference. It was aimed to understand the continuity of care to the preterm newborn in the health care environment in a frontier region in the experience of families and health and nursing professionals. Data collection was done through semi-structured interviews, at the Child Nutrition Center of Foz do Iguaçu, Paraná. The study consisted of seventeen participants, divided into three theoretical samples. The first consisted of eight main caregivers of preterm newborns (mothers), the second consisted of eight health professionals (psychologist, physiotherapist, pediatrician) and nursing professionals (nursing assistants and nurses) and the third had the participation of a manager. Data were collected from July 2016 to March 2017. Data collection and analysis occurred concurrently, according to the method. Having reached the depth of the data, came the understanding of the study. The three interdependent steps of the data analysis were processed: open, axial and selective coding, according to Strauss and Corbin's paradigmatic perspective, which consists of five components (context, causal condition, intervening condition, strategies and consequences), which explain the phenomenon, forming five categories and nine subcategories. The category "Describing the structure and functioning of the Child Nutrition Center of Foz do Iguaçu" forms the context; the category "Preterm birth and the need for care of a preterm newborn" indicates the causal conditions; the category "Identifying conditions that intervene in the process of continuity of care of the preterm newborn" reveals the intervening conditions; the category "Identifying strategies to ensure continuity of care for the preterm newborn" identifies the strategies and the category "Identifying flows of (dis) continuity of care to the preterm newborn in border region" represent the consequences of the phenomenon and also of the central category. It is concluded that the (dis)continuity of care to preterm newborns in the border region presents a disordered and disconnected flow between the care services to the child who was born premature, since hospital discharge. Reference and counter-referral systems seem to be disarticulated, and primary health care has no role in the follow-up of the child and the family at the Child Nutrition Center of Foz do Iguaçu, a reference service for preterm care. Health professionals and managers are required to reflect on the (un)continuity of preterm newborn care, taking into account the multiple social, economic, and health vulnerabilities of individuals in a border region to ensure continued care and interconnected to different health services and meet the multiple needs of the child and his family.